Vitamin K supplementation for metabolic control in patients with Type 2 Diabetes: Systematic review - Condemarin Torres, Kathleen (2023)
Objectives: To determine the effect of vitamin K supplementation on metabolic control in patients with type 2 diabetes mellitus. Materials and methods: Systematic review of randomised controlled trials (RCTs) in five databases. Two authors independently selected studies and extracted information. Risk of bias was performed using the Cochrane collaboration tool. Primary outcomes were need for fasting blood sugar (FBS), total choresterol, high-density lipoprotein (HDL) and low-density lipoprotein (LDL). We used mean difference (MD) to assess the effect on continuous outcomes. We used random-effect model. Results: We included two RCTs (n=100). Vitamin K lowers FPS but it wasn't significant (MD -14.58; IC95% -35.95 to 6.78; p=0.18) in comparison with placebo group. Vitamin K supplement has no significant effect in cholesterol total (MD -1.22; IC95% -21.02 to 18.57; p=0.90), HDL (MD -3.61; IC95% -18.44 to 11.22; p=0.63) and LDL (MD -0.69; IC95% -5.81 to 4.43; p=0.79) levels compared with placebo group. Conclusions: Vitamin K supplement has no effect on metabolic control on patients diagnosed with type 2 diabetes. Keywords: Type 2 diabetes; vitamin K; metabolic control; FBS; lipid profile (Source: MeSH-NLM).